“Come back home early and read for us!” Enabling father-child shared reading in policy and practice - Gallagher, Kay; Dillon, Anna Marie; Saqr, Sumaya; Habak, Claudine; Alramamneh, Yahia (Frontiers in Education, 2025)
This project sought to increase fathers’ involvement in their children’s literacy development through interactive shared reading at home. Parent–child home reading is not a traditional practice in the UAE, and reading attainment is below international standards for children attending state schools. During workshops in Kindergarten schools, simple techniques were shared with fathers for reading picture books in Arabic and English with their bilingual children. Fathers were provided with books to take home to read for pleasure and for information with their children. Recommendations arising include providing guidance on the selection and provision of diverse, contemporary, culturally relevant picture books; holding nationwide reading workshops for both mothers and fathers; and increasing school-home liaison to encompass parents within the literacy development ecosystem in the UAE.